2000
DOI: 10.1001/jama.283.4.506
|View full text |Cite
|
Sign up to set email alerts
|

Mental Disorders and Use of Cardiovascular Procedures After Myocardial Infarction

Abstract: In this study, individuals with comorbid mental disorders were substantially less likely to undergo coronary revascularization procedures than those without mental disorders. Further research is needed to understand the degree to which patient and provider factors contribute to this difference and its implications for quality and long-term outcomes of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
335
12
6

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 473 publications
(377 citation statements)
references
References 51 publications
(40 reference statements)
24
335
12
6
Order By: Relevance
“…33 Consistent with our findings, prior evidence suggests that quality of care for certain conditions that require follow-up with specialists or additional procedures was worse for SMI compared to non-SMI veterans, notably for procedures and medications related to myocardial infarction or coronary artery disease. 14,31 The stigma of mental illness, particularly SMI, may also preclude patients from seeking care outside the comfort zone that exists in the mental health clinic.…”
Section: Discussionmentioning
confidence: 99%
“…33 Consistent with our findings, prior evidence suggests that quality of care for certain conditions that require follow-up with specialists or additional procedures was worse for SMI compared to non-SMI veterans, notably for procedures and medications related to myocardial infarction or coronary artery disease. 14,31 The stigma of mental illness, particularly SMI, may also preclude patients from seeking care outside the comfort zone that exists in the mental health clinic.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the findings noted above 9,20 of lower use of coronary revascularization in patients with inpatient psychiatric codes, Jones and Carney 19 examined privately insured patients with AMI in a single state and found that patients with psychiatric diagnoses captured before or during hospitalization or within 30 days after discharge had similar rates of coronary revascularization. However, in an analysis of VA patients with AMI during 1994-1995, Petersen et al 20 found that patients identified by prior psychiatric admissions, secondary inpatient codes, or mental health provider visits had lower rates of coronary angiography and revascularization but had similar 30-day mortality and were equally likely to receive indicated medications.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, some prior studies have also demonstrated that patients with psychiatric comorbidity identified by secondary inpatient codes had lower mean predicted risk of mortality. 7,9 Second, it is possible that the lower mortality in patients with psychiatric secondary diagnoses may be due to greater vigilance by providers or greater likelihood to admit lower severity patients with psychiatric comorbidities. Third, the 6.5 (7.1) 9.5 (10.5) 7.7 (9.4) 9.8 (10.5) 7.4 (9.4) 9.8 (10.5) *Differences mean ages, laboratory scores, and predicted risks of death for patients with and without psychiatric comorbidity were significant (P<.001) for each of the methods of identifying psychiatric comorbidity for both pneumonia and CHF lower mortality may reflect lower utilization of invasive diagnostic or therapeutic modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among patients with various medical illnesses, those with mental health conditions (MHCs) encounter greater barriers to care, receive less intense management, undergo fewer interventions, and experience worse outcomes. [2][3][4][5][6][7] Factors contributing to some of these observations include non-adherence, fragmentation of care, stigma, and biases. [8][9][10] Warfarin is a widely used anticoagulant, but its utility can only be optimized with regular evaluation and dose adjustment, which promote improved anticoagulation control.…”
Section: Introductionmentioning
confidence: 99%